Groundwater system for the periods of pre- and post-longwall mining over thin overburden. Issue 4 (3rd July 2016) - Li, Yang
Abstract : The groundwater loss is one of the primary issues for environmental destruction. Underground longwall mining methods can cause rapid subsidence of the overburden strata. Especially in shallow coal seam mining. Since the subsidence through the overburden to ground surface, the groundwater may be affected and drawdown into the lower levels above the longwall panels. This paper analysed the potential impact of longwall mining on groundwater over thin overburden. Four water wells were drilled down to the proposed deformation zone above two longwall panels to record the different water levels' variations throughout the mining period. A numerical groundwater flow model (GGU-SS-FLOW3D) was performed to predict the water levels in the periods of pre- and post-mining conditions. To set-up model, local mining conditions and regional geology characteristics were ascertained in this study. The measurement data from the four water wells were adopted to calibrate the flow3D model. The field measurement and GGU-SS-FLOW3D model can help to better understand the variation of the groundwater system related to the ground subsidence from longwall mining over thin overburden.